Lithium nickel manganese oxide positive electrode material, preparation method thereof and electrochemical device

By using high-entropy alloys and high-valent element doping in the nickel-manganate lithium positive electrode material and combining with the cladding technology, the problem of lithium-nickel mixed discharge and side reaction of cobalt-free ternary lithium-ion battery positive electrode material after cobalt loss is solved. , improves the cycle stability and thermal stability of the battery.

CN119297246APending Publication Date: 2025-01-10NANTONG RESHINE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411458273.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The cobalt-free ternary lithium-ion battery positive electrode material causes serious lithium-nickel mixed discharge after cobalt loss, the battery capacity rapidly attenuates, the material impedance increases, resulting in a decrease in rate performance, and the side reaction with the electrolyte leads to a decrease in stability.

Method used

Nickel-manganate positive electrode material is used to form a high-entropy alloy through co-doping of multiple elements, increasing the coordination environment diversity of oxygen, inhibiting oxygen precipitation and transition metal migration, and using high-valent element doping and cladding to reduce Side reactions form a stable layered structure.

Benefits of technology

The cycle stability and thermal stability of the nickel-manganese oxide cathode material are improved, the lithium-nickel mixed discharge is reduced, the cycle life of the battery is extended, and the energy density loss of the battery is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297246A_ABST
    Figure CN119297246A_ABST
Patent Text Reader

Abstract

The lithium nickel manganese oxide positive electrode material comprises an inner core and a coating layer located on the surface of the inner core, the inner core is a high-entropy doped cobalt-free ternary single-crystal positive electrode material, the chemical formula of the inner core is Li (NiaMnbT1-a-b) O2, the inner core has a stable layered structure, and the coating layer outside the inner core can inhibit side reaction between a cobalt-free positive electrode and an electrolyte interface, so that the electrochemical performance of the lithium nickel manganese oxide positive electrode material is improved. The inner core adopts high-entropy doping to inhibit lattice anisotropic distortion and lattice collapse in a cobalt-free positive electrode charging process, so that the cycling stability of the cobalt-free positive electrode is improved; according to the cobalt-free ternary positive electrode material, the morphology and arrangement of single-crystal primary particles are changed, and the instability of a ternary layered structure caused by Co element deficiency is inhibited, so that a microstructure with better mechanical property and cycle performance is formed, and the problem of serious lithium-nickel mixed arrangement caused by cobalt deficiency of the cobalt-free ternary positive electrode material is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy materials, and in particular to a lithium nickel manganese oxide positive electrode material and a preparation method and an electrochemical device thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in the fields of electronic products and new energy vehicles. Lithium-ion battery cathode materials are an important component of lithium-ion batteries. Commonly used lithium-ion battery cathode materials include lithium cobalt oxide, nickel-cobalt-manganese ternary cathode materials (NCM) and nickel-cobalt-aluminum ternary cathode materials (NCA). Cobalt, as one of the key components of ternary cathode materials, has the function of stabilizing the structure. However, cobalt resources face problems such as limited reserves on the earth, higher prices than nickel, manganese and other elements, and high volatility. Therefore, removing cobalt from ternary cathodes is an urgent need for economical and sustainable lithium-ion batteries.

[0003] However, there are still some problems with cobalt-free ternary cathode materials that make it difficult to meet commercial needs. For example, the lack of cobalt causes more serious lithium-nickel mixing, which causes the battery capacity to decay rapidly. At the same time, the material impedance increases, resulting in a decrease in battery rate performance; + The embedding and extraction of positive electrodes cause the anisotropy of the lattice parameters to change, and the stability of the positive electrode materials to decrease during long-term cyclic use; the side reactions between the positive electrode materials and the electrolyte will also cause the battery capacity to decay and the thermal stability to decrease. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a lithium nickel manganese oxide positive electrode material.

[0005] In addition, the embodiments of the present application also provide a method for preparing the aforementioned lithium nickel manganese oxide positive electrode material, and an electrochemical device using the lithium nickel manganese oxide positive electrode material.

[0006] The present invention provides a lithium nickel manganese oxide positive electrode material, comprising a core and a coating layer located on at least a portion of the surface of the core, wherein the chemical formula of the core is Li(Ni a Mn b T 1-a-b )O2, wherein 0.6≤a≤0.8, 0.25≤b≤0.35, 0.05≤1-ab≤0.1, the transition element T includes at least 3 of Mg, Zr, Al, Ti, Nb, Ta, Sb, V, Mo and W, and the content of each transition element T is 0.01-0.02.

[0007] In some possible embodiments, the transition element T is a combination of Mg, Al, and Nb; or, the transition element T is a combination of Mo, Ti, Sb, and W.

[0008] In some possible embodiments, the coating layer includes one or more of W, La, Gd, Ru, Ce, and Nb.

[0009] The present application also provides a method for preparing a lithium nickel manganese oxide positive electrode material, comprising: mixing a lithium source, nickel manganese hydroxide and an oxide containing a transition element T, and pre-sintering to obtain a precursor; mixing the precursor with a solvent and then sintering to obtain a single crystal core; providing a coating material on at least a portion of the surface of the single crystal core and re-sintering to obtain a lithium nickel manganese oxide positive electrode material; wherein the chemical formula of the lithium nickel manganese oxide positive electrode material is Li(Ni a Mn b T 1-a-b )O2, wherein 0.6≤a≤0.8, 0.25≤b≤0.35, 0.05≤1-ab≤0.1, the transition element T includes at least three of Mg, Zr, Al, Ti, Nb, Ta, Sb, V, Mo and W, and the content of each transition element T is 0.01-0.02.

[0010] In some possible embodiments, the sintering temperature of the pre-sintering is 400° C.-700° C., and the holding time is 3-10 hours.

[0011] In some possible embodiments, the co-solvent includes one or more oxides or carbonates of Sr, Sn, and Ba.

[0012] In some possible embodiments, the sintering temperature of the sintering treatment is 800° C.-900° C., and the holding time is 3-10 hours.

[0013] In some possible embodiments, the re-sintering process includes mixing the coating material of the coating element M with the single crystal core, sintering and keeping warm at a temperature of 300°C-600°C for 3-10 hours; the coating material includes one or more of W, La, Gd, Ru, Ce and Nb.

[0014] In some possible embodiments, the specific surface area of ​​the precursor is > 2 m 2 / g.

[0015] In addition, an embodiment of the present application further provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte. The positive electrode plate includes a positive electrode active material, and the positive electrode active material is the aforementioned lithium nickel manganese oxide positive electrode material.

[0016] Compared with the prior art, the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application has a stable layered structure. By co-doping multiple elements to form a high-entropy alloy, a disordered state can be formed locally inside the lithium nickel manganese oxide positive electrode material, thereby increasing the diversity of the coordination environment of oxygen in the lithium nickel manganese oxide positive electrode material, thereby inhibiting oxygen precipitation, reducing the phase change caused by transition metal migration, and improving the stability of the layered structure, thereby improving the problem of serious lithium-nickel mixing caused by cobalt deficiency in cobalt-free ternary positive electrode materials during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a process flow chart of the method for preparing the nickel manganese oxide lithium positive electrode material provided in an embodiment of the present application.

[0018] Figure 2 This is a schematic diagram of the structure of the electrochemical device provided in an embodiment of the present application.

[0019] Figure 3 This is a schematic diagram of the cross-sectional structure of the lithium nickel manganese oxide positive electrode material provided in an embodiment of the present application.

[0020] Figure 4 This is a scanning electron microscope image of the lithium nickel manganese oxide positive electrode material of Example 1 of the present application.

[0021] Figure 5 This is a scanning electron microscope image of the lithium nickel manganese oxide positive electrode material of comparative example 1 of the present application.

[0022] Figure 6 It is a comparison chart of the cycle capacity retention rate curves at 45°C of batteries prepared with the nickel manganese oxide positive electrode materials in Examples 1-2 and Comparative Examples 2-3 of the present application.

[0023] Figure 7 This is a comparison chart of the DSC curves of the lithium nickel manganese oxide positive electrode materials in Examples 1-2 and Comparative Examples 2-3 of the present application. DETAILED DESCRIPTION

[0024] The following will clearly and completely describe the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments.

[0025] Ternary nickel manganese oxide cathode materials show good comprehensive performance in terms of energy density, cycle stability and safety. However, cobalt-free ternary cathode materials still have some problems that make it difficult to meet commercial needs. For example, the lack of cobalt causes more serious lithium-nickel mixing, which causes the battery capacity to decay rapidly. At the same time, the material impedance increases, resulting in a decrease in battery rate performance. +The embedding and extraction of the positive electrode material will cause the anisotropy of the lattice parameters to change, and the stability of the positive electrode material will be reduced in long-term cyclic use; the side reaction between the positive electrode material and the electrolyte will also cause the battery capacity to decay and the thermal stability to decrease. In order to overcome the above problems, the current application number is CN202410649999.6, and the related technology of the invention titled "A lithium-rich, cobalt-free, high-entropy doped positive electrode material and its preparation method and application" increases the intralayer configuration entropy of the material, increases the diversity of the local environment to stabilize the lattice oxygen, inhibits the capacity and voltage decay, and promotes the commercial application of low-cost, high-energy-density lithium-rich positive electrode materials.

[0026] The inventors of this application have found that polycrystalline positive electrode materials are usually secondary spherical polycrystalline particles formed by the aggregation of many primary nano-scale particles. Therefore, the most common failure mechanism is particle cracking, which increases the contact area between the inside of the particles and the electrolyte and causes serious side reactions, affecting the cycle performance. However, since single-crystal positive electrode materials do not have grain boundaries and the structure of single-crystal particles is overall stable, they have become the only choice for projects with high requirements for long-cycle performance, such as energy storage. Although the above-mentioned high-entropy doping method can solve the problem of serious lithium-nickel mixing and increased impedance of positive electrode materials caused by the lack of cobalt in the use of cobalt-free ternary positive electrode materials to a certain extent, it cannot solve the problem of increased side reactions between positive electrode materials and electrolytes.

[0027] To do this, see Figure 3 The nickel manganese oxide positive electrode material provided in the embodiment of the present application includes a core 1 and a coating layer 2 located on at least a portion of the surface of the core 1, wherein the core 1 is a high entropy doped cobalt-free ternary single crystal positive electrode material, and the chemical formula of the core 1 is Li(Ni a Mn b T 1-a-b)O2, wherein 0.6≤a≤0.8, 0.25≤b≤0.35, 0.05≤1-ab≤0.1, the transition element T includes at least three transition elements of Mg, Zr, Al, Ti, Nb, Ta, Sb, V, Mo and W, and the number of atoms of each transition element T in the above chemical formula is between 0.01 and 0.02. That is, by co-doping multiple elements to form a high-entropy alloy, a disordered state can be formed locally inside the lithium nickel manganese oxide positive electrode material, increasing the diversity of the coordination environment of oxygen in the lithium nickel manganese oxide positive electrode material, thereby inhibiting oxygen precipitation, reducing the phase change caused by transition metal migration, and improving the stability of the layered structure, thereby improving the problem of serious lithium-nickel mixing caused by cobalt deficiency in the use of cobalt-free ternary positive electrode materials. At the same time, by limiting the number of atoms of each T element in the above chemical formula, a disordered state can be formed locally inside the lithium nickel manganese oxide positive electrode material, increasing the diversity of the coordination environment of oxygen in the lithium nickel manganese oxide positive electrode material. If the content of each T element is too low, the beneficial effect of high entropy doping cannot be achieved; if the content of each T element is too high, it will lead to the formation of impurity phases.

[0028] On the one hand, Mg 2+ 、Zn 2+ 、Al 3+ 、Ti 4+ Plasma doping can inhibit the lattice anisotropy distortion and lattice collapse during the charging process of the cobalt-free positive electrode, thereby improving its cycle stability; Nb 5+ 、 5+ , Sb 5+ 、V 5+ 、Mo 6+ , W 6+ Ion doping with high-valent ions can change the morphology and arrangement of single crystal primary particles, inhibit the instability of the ternary layered structure caused by the lack of cobalt elements, and thus form a microstructure with better mechanical properties and cycle performance.

[0029] On the other hand, the use of coating materials on the surface of the single crystal can reduce the side reactions between the electrolyte and the positive electrode material during charging and discharging, further improving the cycle performance of the lithium nickel manganese oxide positive electrode material, thereby improving the problems of capacity attenuation and reduced thermal stability caused by the side reactions between the positive electrode material and the electrolyte.

[0030] In some embodiments, the transition element T is a combination of Mg, Al, and Nb; or, the transition element T is a combination of Mo, Ti, Sb, and W. Therefore, there is a synergistic effect between the above T elements, which can eliminate the microstress of the grain boundary while maintaining the stability of the layered structure, so that the cycle retention rate and thermal stability of the battery are better.

[0031] In some embodiments, the coating layer is a coating material containing a coating element M, and the coating element M includes one or more of W, La, Gd, Ru, Ce, and Nb, and the corresponding metal compound can form a solution or suspension in water. The oxide coating layer formed by the high-priced coating elements W, La, Gd, Ru, Ce, and Nb after re-sintering can inhibit the side reaction between the cobalt-free positive electrode material and the electrolyte, and further improve the cycle performance. Moreover, the coating element M is a transition metal element with a large atomic radius. Since the atomic radius is larger than the interlayer spacing of the positive electrode material, it can only be coated on the surface of the single crystal to form a coating layer, and cannot diffuse into the lattice.

[0032] In some embodiments, the thickness of the coating layer can be 2nm~6nm. Within the above range, it can avoid the coating layer being too thin (less than 2nm) and unable to effectively isolate the electrolyte or provide sufficient ionic conductivity; at the same time, it can also avoid the coating layer being too thick (greater than 6nm) causing the internal impedance of the lithium nickel manganese oxide positive electrode material to increase, thereby affecting the energy density and overall performance of the lithium nickel manganese oxide positive electrode material.

[0033] Compared with the prior art, the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By co-doping multiple elements to form a high-entropy alloy, the intralayer configuration entropy of the positive electrode material can be improved, the local environment diversity can be increased, the lattice oxygen can be stabilized, the capacity decay can be inhibited, and the commercial application of low-cost, high-cycle performance cobalt-free ternary positive electrode materials can be promoted.

[0034] 2. When doping with high-valent elements, the grain morphology can be optimized, the lattice anisotropic distortion and lattice collapse during the charging process of the cobalt-free positive electrode can be suppressed, the unfavorable transformation of the positive electrode material from layered to rock salt phase can be suppressed, and the instability of the ternary layered structure caused by the lack of Co element can be improved, thereby forming a microstructure with better mechanical properties and cycle performance.

[0035] See also Figure 1 As shown, the preparation method of the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application specifically includes the following steps: Step S1: Mix a lithium source, nickel manganese hydroxide and an oxide containing a transition element T, and pre-sinter them to obtain a precursor.

[0036] Specifically, the pre-sintering process includes putting the lithium source, nickel manganese hydroxide and T oxide into a high-speed mixer for uniform mixing, sintering and keeping warm at 400°C-700°C after mixing, and the holding time is 3-10h; in some optional embodiments, the sintering temperature can be 400°C, 600°C, 700°C, and in some optional embodiments, the holding time is 3h, 5h, 8h, 10h. Through the pre-sintering treatment, the crystal water in the lithium salt can be removed, and the nickel manganese hydroxide can be dehydrated into oxides, increasing the specific surface area of ​​the precursor, so that it can be in close contact with the lithium salt and the doping elements, improving the reaction diffusion efficiency, and avoiding the generation of impurity phases. Due to the increase in bulk density after pretreatment dehydration, when the single crystal is formed by subsequent high-temperature sintering, the amount of material added to the sagger can be increased, thereby greatly improving the production capacity and reducing energy consumption.

[0037] In some embodiments, the nickel manganese hydroxide is a nickel manganese hydroxide with a nickel-manganese molar ratio of 75:25. In some optional embodiments, the nickel-manganese molar ratio is 70:30. The lithium source can be micro powder lithium hydroxide.

[0038] In some embodiments, the transition element T includes at least three of Mg, Zr, Al, Ti, Nb, Ta, Sb, V, Mo and W, and the content of each transition element T is 0.01-0.02. In some optional embodiments, the transition element T can be a combination of Mg, Al, Nb, or a combination of Mo, Ti, Sb, W, Mg 2+ 、Zn 2+ 、Al 3+ 、Ti 4+ Plasma doping can inhibit the lattice anisotropy distortion and lattice collapse during the charging process of the cobalt-free positive electrode, thereby improving its cycle stability; Nb 5+ 、 5+ , Sb 5+ 、V 5+ 、Mo 6+ , W 6+ Doping with high-valent ions can optimize the grain morphology. By changing the morphology and arrangement of single crystal primary particles, it can inhibit the instability of the ternary layered structure caused by the lack of cobalt, thereby forming a microstructure with better mechanical properties and cycle performance. There is a synergistic effect between the above-mentioned T elements, which can eliminate the grain boundaries and improve microstress while maintaining the stability of the layered structure, thereby improving the cycle retention rate and thermal stability of the battery.

[0039] Furthermore, the surface area of ​​the precursor is > 2m 2 / g, in some optional embodiments, the specific surface area of ​​the precursor can be 2.1 m 2 / g, 3.0 m 2 / g, 5.0 m 2 / g.

[0040] Step S2: Mix the precursor and the solvent and then sinter to obtain a single crystal core.

[0041] Specifically, after the precursor and the solvent are mixed, they are placed in a sintering device (such as a roller kiln) for sintering at a temperature of 800°C-900°C for 5-10 hours. After the sintering is completed, a single crystal core is obtained.

[0042] In some optional embodiments, the sintering atmosphere can be oxygen or air. In some optional embodiments, the sintering temperature can be 800°C or 900°C. In some optional embodiments, the holding time can be 5h, 7h, 8h, or 10h. Appropriate sintering temperature and holding time can help form a single crystal core.

[0043] Furthermore, the solvent exists in the form of one or more oxides or carbonates of Sr, Sn, and Ba. In some optional embodiments, the solvent exists in the form of SrO2, SrCO3, SnO2, or SnCO3. By using the solvent, the sintering temperature for forming single crystals can be lowered, thereby promoting the formation and improvement of single crystal particles.

[0044] Further, the concentration of the co-solvent is 500-800 ppm. In some optional embodiments, the concentration of the co-solvent may be 500 ppm, 600 ppm, or 800 ppm.

[0045] Step S3: mixing the coating material containing the coating element M with the single crystal core by spray coating and re-sintering to obtain a lithium nickel manganese oxide positive electrode material.

[0046] Specifically, the single crystal core and the coating material containing the coating element M are uniformly mixed and coated by a spray coating process, and then re-sintered to obtain a lithium nickel manganese oxide positive electrode material with a high entropy element coating layer.

[0047] Furthermore, the coating element M includes one or more of W, La, Gd, Ru, Ce, and Nb, and the corresponding metal compounds can form a solution or suspension in water. Exemplary ones are W, La, Gd, Ru, Ce, and Nb. The oxide coating layer formed after the re-sintering treatment of these high-priced coating elements can inhibit the side reaction between the cobalt-free positive electrode and the electrolyte, and further improve the cycle performance. The coating element M is a transition metal element with a larger atomic radius. Since the atomic radius is larger than the interlayer spacing of the positive electrode material, it can only be coated on the surface of the single crystal core to form a coating layer, and cannot diffuse into the lattice. The doping of the doping element T acts on the single crystal core lattice and the grain boundary, while the coating element acts on the outer surface to inhibit the side reaction between the cobalt-free positive electrode and the electrolyte.

[0048] In some optional embodiments, the coating material containing the coating element M may be a coating material containing the coating element W 6+ 、Ce 4+ The coating solvent and suspension have a concentration of each element of 500-3000ppm, and more preferably, the concentration of each coating element is 1000ppm.

[0049] Further, the temperature condition of the re-sintering treatment is 300°C-600°C. In some optional embodiments, the temperature of the re-sintering treatment can be 300°C, 500°C, 600°C, and the holding time is 3-10h. In some optional embodiments, the holding time can be 3h, 5h, 10h. The appropriate sintering time can ensure the full reaction of the coating layer and further improve the uniformity, stability and density of the coating layer. Sintering under the above parameters is conducive to improving the comprehensive effect of the coating, improving the quality of the coating layer, and thus improving the comprehensive performance of the lithium nickel manganese oxide positive electrode material.

[0050] Compared with the prior art, the preparation method of the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. Pre-sintering treatment can remove the crystal water in the lithium salt and dehydrate the nickel manganese hydroxide into oxides, increase the specific surface area of ​​the precursor, and make it closely contact with the lithium salt and doping elements, improve the reaction diffusion efficiency, and avoid the generation of impurity phases. Due to the increase in bulk density after pre-treatment dehydration, the amount of material added to the sagger can be increased during the subsequent high-temperature sintering to form a single crystal, thereby greatly increasing production capacity and reducing energy consumption.

[0051] 2. The single crystal core and the coating material containing the coating element M are uniformly mixed and coated by a spray coating process, and then sintered multiple times. The oxide coating layer formed by the high-priced coating element after re-sintering can inhibit the side reaction between the cobalt-free positive electrode and the electrolyte, and further improve the cycle performance. The coating element M is a transition metal element with a larger atomic radius. Since the atomic radius is larger than the interlayer spacing of the positive electrode material, it can only be coated on the surface of the single crystal core to form a coating layer.

[0052] 3. The preparation method is simple and efficient, which is conducive to the large-scale production of lithium nickel manganese oxide positive electrode materials and has excellent commercial prospects.

[0053] See also Figure 2As shown, the embodiment of the present application also provides an electrochemical device (such as a battery), the electrochemical device 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the positive electrode sheet 10 includes a positive electrode active material, and the positive electrode active material is the above-mentioned lithium nickel manganese oxide positive electrode material. The electrochemical device 100 prepared using the above-mentioned lithium nickel manganese oxide positive electrode material has the advantages of high capacity, high initial efficiency, long cycle life and excellent rate performance.

[0054] The above-mentioned lithium nickel manganese oxide positive electrode material and its preparation method and electrochemical device are further described below through specific examples.

[0055] Example 1 Step 1: 10 kg of Ni 0.75 Mn 0.25 (OH)2, 4.75kg of micro powder lithium hydroxide and doping element Mg 2+ 、Al 3+ , Nb 5+ 1 mol% of each was put into a high-speed mixer to mix evenly, and pre-sintered to obtain a specific surface area of ​​2m 2 / g precursor; Step 2: 10.6kg specific surface area>2m 2 / g of the precursor was mixed with a 500ppm Sr co-solvent and sintered at 900℃ in a pure oxygen atmosphere for 10h to obtain a single crystal core; Step 3: Combine the single crystal core with the coating element W 6+ 、Ce 4+ 1000ppm of each coating solvent and suspension were uniformly mixed and coated by a spray coating process at a coating temperature of 500°C, and then re-sintered at a sintering temperature of 500°C for 6 hours to obtain a lithium nickel manganese oxide positive electrode material with a W / Ce high entropy element coating layer.

[0056] Example 2 Step 1: 10 kg of Ni 0.75 Mn 0.25 (OH)2, 4.75kg of micro powder lithium hydroxide and doping element Mo 6+ 、Ti 4+ , Sb 5+ , W 6+ 1 mol% of each was put into a high-speed mixer to mix evenly, and pre-sintered to obtain a specific surface area of ​​2m 2 / g precursor; Step 2: 10.6kg specific surface area>2m 2 / g of the precursor was mixed with a 500ppm Sr co-solvent and sintered at 900℃ in a pure oxygen atmosphere for 10h to obtain a single crystal core; Step 3: Combine the single crystal core with the coating element W 6+ 、Ce 4+ 1000ppm of each coating solvent and suspension were uniformly mixed and coated by a spray coating process at a coating temperature of 500°C, and then re-sintered at a sintering temperature of 500°C for 6 hours to obtain a lithium nickel manganese oxide positive electrode material with a W / Ce high entropy element coating layer.

[0057] Comparative Example 1 The specific process of the preparation process refers to Example 1, except that in step 2, no solvent is added and high-temperature sintering is directly performed. The preparation method of the rest of the lithium nickel manganese oxide positive electrode material is basically the same as that of Example 1, and will not be described in detail here.

[0058] Comparative Example 2 The specific process of the preparation process refers to Example 1, except that no high entropy element is added for doping in step 1. The preparation method of the remaining lithium nickel manganese oxide positive electrode materials is basically the same as that of Example 1, and will not be described in detail here.

[0059] Comparative Example 3 The specific process of the preparation process refers to Example 1, except that no high entropy element coating is performed in step 3. The preparation method of the remaining lithium nickel manganese oxide positive electrode materials is basically the same as that in Example 1, and will not be described in detail here.

[0060] The following tests were performed on the lithium nickel manganese oxide positive electrode materials obtained in Example 1 and Comparative Examples 1-3.

[0061] The nickel manganese oxide positive electrode material prepared in Example 1 was subjected to SEM testing, and the results were as follows: Figure 4 As shown; the nickel manganese oxide lithium positive electrode material prepared in Comparative Example 1 was subjected to SEM testing, and the results are as follows Figure 5 shown.

[0062] The electrical performance test conditions are as follows: The positive electrode materials corresponding to Examples 1-2 and Comparative Examples 2-3 are made into positive electrode sheets respectively, and metal lithium is used as the negative electrode to assemble button-type batteries. At an ambient temperature of 45°C, in the voltage range of 2.8 to 4.4V, the button-type batteries of Examples 1, 2 and Comparative Examples 2, 3 are subjected to a cycle performance test (1C / 1C cycle test) at a current density of 1C, and the capacity retention rate of each button-type battery is calculated after 100 cycles.

[0063] After fully charging the batteries of Example 1-2 and Comparative Example 2-3 within the voltage range of 2.8 to 4.4 V, the batteries were disassembled to obtain the positive electrode materials after charging and delithiation, which were placed in a crucible together with the electrolyte for DSC testing.

[0064] The above results show that: See also Figure 4 , Figure 5 The surface morphologies of the lithium nickel manganese oxide positive electrode materials after coating and sintering of Example 1 and Comparative Example 1 are compared. Both positive electrode materials of Example 1 and Comparative Example 1 are composed of 1-10 μm particles and have a single crystal morphology, among which the particles of Example 1 have significantly better roundness, indicating that the addition of flux is beneficial to the formation and improvement of cobalt-free single crystal particles.

[0065] See also Figure 6 By comparing Example 1, Example 2 and Comparative Example 2, Comparative Example 3, it can be found that the cycle performance of Examples 1 and 2 doped with high entropy elements is significantly improved, which is suitable for the application of low-cost long-cycle positive electrode materials.

[0066] See also Figure 7 The results show that the reaction exothermic peaks on DSC corresponding to Examples 1 and 2 are both split double peaks, while the reaction exothermic peaks corresponding to Comparative Examples 2 and 3 are both single peaks, and the exothermic peak of Example 3 is sharper, and the initial reaction temperature is earlier, indicating that both high-entropy element doping and coating can inhibit the side reactions between the active material and the electrolyte, and improve the cycle and safety performance.

[0067] It can be seen that compared with comparative examples 1-3, the nickel manganese oxide positive electrode material obtained in Example 1 has excellent performance and electrochemical test results due to the high entropy element doping and the high-valent element coating formed after spray coating, indicating that the rate performance and stability of the nickel manganese oxide positive electrode material in the examples of the present application during long-term cycling are improved.

[0068] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A lithium nickel manganese oxide positive electrode material, characterized in that: It comprises a core and a coating layer located on at least a portion of the surface of the core, wherein the chemical formula of the core is Li(Ni a Mn b T 1-a-b )O2, wherein 0.6≤a≤0.8, 0.25≤b≤0.35, 0.05≤1-ab≤0.1, the transition element T includes at least three of Mg, Zr, Al, Ti, Nb, Ta, Sb, V, Mo and W, and the content of each transition element T is 0.01-0.

02.

2. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that The transition element T is a combination of Mg, Al, and Nb; or, the transition element T is a combination of Mo, Ti, Sb, and W.

3. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The coating layer includes one or more of W, La, Gd, Ru, Ce, and Nb.

4. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: include: A lithium source, nickel manganese hydroxide and an oxide containing a transition element T are mixed and pre-sintered to obtain a precursor; The precursor is mixed with a co-solvent and then sintered to obtain a single crystal core; Arranging a coating material on at least a portion of the surface of the single crystal core and performing a re-sintering process to obtain a lithium nickel manganese oxide positive electrode material; Among them, the chemical formula of lithium nickel manganese oxide positive electrode material is Li(Ni a Mn b T 1-a-b )O2, wherein 0.6≤a≤0.8, 0.25≤b≤0.35, 0.05≤1-ab≤0.1, the transition element T includes at least three of Mg, Zr, Al, Ti, Nb, Ta, Sb, V, Mo and W, and the content of each transition element T is 0.01-0.

02.

5. The method for preparing the lithium nickel manganese oxide positive electrode material according to claim 4, characterized in that: The sintering temperature of the pre-sintering is 400° C.-700° C., and the heat preservation time is 3-10 hours.

6. The method for preparing the lithium nickel manganese oxide positive electrode material according to claim 4, characterized in that: The co-solvent includes one or more oxides or carbonates of Sr, Sn, and Ba.

7. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 4, characterized in that: The sintering temperature of the sintering treatment is 800° C.-900° C., and the heat preservation time is 3-10 hours.

8. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 4, characterized in that: The sintering temperature of the re-sintering treatment is 300°C-600°C, and the holding time is 3-10h; The coating material includes one or more of W, La, Gd, Ru, Ce and Nb.

9. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 4, characterized in that: The specific surface area of ​​the precursor is > 2m 2 / g.

10. An electrochemical device, characterized in that: The electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet includes a positive electrode active material. The positive electrode active material is a lithium nickel manganese oxide positive electrode material as described in any one of claims 1 to 3 or a lithium nickel manganese oxide positive electrode material prepared by the preparation method of the lithium nickel manganese oxide positive electrode material as described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Lithium-rich cobalt-free high-entropy doped positive electrode material as well as preparation method and application thereof

    CN118507688A

Cited By

  • Monocrystal lithium nickel manganese oxide positive electrode material, preparation method thereof and lithium ion battery

    CN122619763A

  • A high-tropical single-crystal cathode active material with core-shell structure for LMFP / LFP and NCMA / NMx

    DE102024126096A1